Atomic-scale and damage-free polishing of single crystal diamond enhanced by atmospheric pressure inductively coupled plasma. (September 2021) - Luo, Hu; Ajmal, Khan Muhammad; Liu, Wang; Yamamura, Kazuya; Deng, Hui
Abstract: Diamond is an imperative material for fabricating functional components used in ultra-hard cutting tools, infrared optical windows, high-performance heat dissipations, and other fields. However, high surface roughness caused by competitive crystal growth in diamonds is troublesome. Besides, diamond polishing is challenging due to extreme hardness and chemical inertness. This work is focused on highly efficient and damage-free diamond polishing enhanced by atmospheric pressure inductively coupled plasma (ICP) modified silicon plate. A rapid decrease in the surface roughness from S a 308 nm–0.86 nm over 300 μm 2 in 120 min proclaims ICP enhanced polishing a highly efficient technique. Simultaneously, an atomically smooth, high-quality diamond surface is obtained with a surface roughness of R a 0.26 nm over 20 μm 2 . The polishing mechanism based on the OH∗ modification of silicon plate and diamond surface, dehydration condensation reaction occurring at the interface of OH∗ terminated surfaces, and subsequent mechanical shearing of carbon, is proposed. The optical emission spectra of ICP, and XPS of the polished diamond surface endorse the material removal mechanism. The TEM and Raman analysis of the ICP enhanced polished surfaces promote the damage-free removal of the mechanically induced damaged layer. The ICP enhanced polishing with modified silicon plate shows great potential in damage-free atomic processing and a promising future as a commercial diamond polishing technique. Graphical abstract: Image 1